2019
DOI: 10.2151/sola.2019-037
|View full text |Cite
|
Sign up to set email alerts
|

Interannual Variation of Upper Tropospheric CO over the Western Pacific Linked with Indonesian Fires

Abstract: We analyzed temporal variations of carbon monoxide (CO) in the upper troposphere from 30°N to 30°S observed using instruments aboard commercial airliner flights between Japan and Australia over the period 1993−2016. Here we focused on the CO variations in the Southern Hemisphere (SH) that showed a unique seasonal cycle with an increased CO around October-November every year. The seasonal CO peaks in the SH showed significant interannual variability (IAV), and are notably enhanced in strong El Niño years, espec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Given the sparse ground-based observations in Equatorial Asia, these programmes provide valuable opportunities to investigate the fire-induced emissions in the region. The long-term aircraft observation (the predecessor of CONTRAIL) observed CO2 and CO mole fraction variations associated with El Niño over the western Pacific since 1993 (Matsueda et al, 2002(Matsueda et al, , 2019. Its occasional observation flight to Singapore (Matsueda and Inoue, 1999) and a campaign flight over Australia and Indonesia (Sawa et al, 1999) captured pronounced elevations of CO from the Equatorial fires in 1997.…”
mentioning
confidence: 99%
“…Given the sparse ground-based observations in Equatorial Asia, these programmes provide valuable opportunities to investigate the fire-induced emissions in the region. The long-term aircraft observation (the predecessor of CONTRAIL) observed CO2 and CO mole fraction variations associated with El Niño over the western Pacific since 1993 (Matsueda et al, 2002(Matsueda et al, , 2019. Its occasional observation flight to Singapore (Matsueda and Inoue, 1999) and a campaign flight over Australia and Indonesia (Sawa et al, 1999) captured pronounced elevations of CO from the Equatorial fires in 1997.…”
mentioning
confidence: 99%
“…Large-scale dynamics and circulations can play a crucial role in transporting Indonesian pollution to long-distance downwind regions (Bowman, 2006;Nara et al, 2011;Matsueda et al, 2019). To understand the plausible mechanisms behind the transport of Indonesian fire pollution to LABS, we further examined the MERRA-2 reanalysis of geopotential height (GpH of the high-pressure anti-cyclone over SCS.…”
Section: Role Of Large-scale Dynamics and Atmospheric Circulationsmentioning
confidence: 99%
“…The lifetime of CO in the free troposphere is ∼ two months, thus can be a tracer from polluted upwind regions to remote downwind areas (Cooper et al, 2012). Some of the studies reported the influence of Indonesian fire activity and the transport of CO from Indonesia to the Indian Ocean, Southern Pacific, and western Pacific Ocean (Matsueda and Inoue, 1999;Pochanart and Akimoto, 2003;Nara et al, 2011;Matsueda et al, 2002Matsueda et al, , 2019. However, the underlying transport mechanisms sending this fire pollution to downwind northern hemisphere subtropical locations, particularly transport to high-altitude background locations in the western north Pacific are still unclear.…”
mentioning
confidence: 99%
“…The lifetime of CO in the free troposphere is ∼ 2 months and can thus be a tracer from polluted upwind regions to remote downwind areas (Cooper et al, 2012). Some of the studies reported the influence of Indonesian fire activity and the transport of CO from Indonesia to the Indian Ocean, Southern Pacific, and western Pacific Ocean (Matsueda and Inoue, 1999;Pochanart et al, 2003;Nara et al, 2011;Matsueda et al, 2002Matsueda et al, , 2019. However, the underlying transport mechanisms sending this fire pollution to downwind Northern Hemisphere subtropical locations, particularly in the form of transport to high-altitude background locations in the western North Pacific are still unclear.…”
Section: Introductionmentioning
confidence: 99%